ANALISIS PENGARUH WEBSITE QUALITY, PERSEPSI HARGA DAN WORD 0F MOUTH TERHADAP KEPUTUSAN PEMBELIAN DI MATAHARI - Suger Suranto; Suharto; Samlawi (Sekolah Tinggi Ilmu Ekonomi Bisnis Indonesia, 2021)
The purpose of this study was to determine the effect of Website Quality on Purchase Decisions, the effect of Price Perception on Purchase Decisions, the influence of Word of Mouth on Purchase Decisions and the influence of Website Quality, Price Perception, and Word of Mouth on purchasing decisions at Matahari.com. This study used 100 respondents online customers of Matahari.com, with multiple regression methods with data processing tools using SPSS 22. The results showed that Website Quality variables had a significant influence on purchasing decisions. Price Perception Variables have a significant influence on purchasing decisions. Word of Mouth variables have a significant influence on purchasing decisions. Website Quality, Price Perception, Word of Mouth simultaneously have a significant effect on Purchase Decisions.